2007
DOI: 10.4314/ajtcam.v4i1.31191
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic effect of <i>Ceiba pentandra</i> extract on streptozo-tocin-induced non-insulin-dependent diabetic (niddm) rats

Abstract: The aim of this work was to investigate the effect of daily oral administration of root bark methylene chloride/methanol extract of Ceiba pentandra (Linn) in streptozotocin-induced type-2 diabetic rats, and the effect of this treatment on the physiological and metabolic parameters that are related in diabetic animals. The diabetic rats were separated into four groups and each given the following samples by gavage, daily for 28 days: vehicle (diabetic control), Ceiba pentandra extract at the dose of 40 mg/kg, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 16 publications
(11 reference statements)
1
11
0
Order By: Relevance
“…Moreover, the extract prevented the increase in the serum glucose level induced by chronic ethanol and sucrose feeding suggesting its hypoglycaemic activity. The improvement of blood glucose level induced by the aqueous extract was associated with a reduction of serum triglycerides and total cholesterol as previously mentioned for most hypoglycaemic treatments [ 37 ]. The glucose lowering effect of the extract may be due to its ability to improve the function of pancreatic β cells by increasing cells sensitivity to insulin and/or the rate of glucose transport and utilization [ 14 ].…”
Section: Discussionmentioning
confidence: 71%
“…Moreover, the extract prevented the increase in the serum glucose level induced by chronic ethanol and sucrose feeding suggesting its hypoglycaemic activity. The improvement of blood glucose level induced by the aqueous extract was associated with a reduction of serum triglycerides and total cholesterol as previously mentioned for most hypoglycaemic treatments [ 37 ]. The glucose lowering effect of the extract may be due to its ability to improve the function of pancreatic β cells by increasing cells sensitivity to insulin and/or the rate of glucose transport and utilization [ 14 ].…”
Section: Discussionmentioning
confidence: 71%
“…Likewise, the improvements in pancreas weights of diabetic rats subsequent to administration of the leaf extracts suggested extra-pancreatic mechanisms of action of V. album as previously posited elsewhere. [11,54,55] It is worthwhile to note that within the ambit of alterations in visceral organ weight as a basis for toxicologic assessment of V. album leaf extracts, indicators showed that administration of the leaf extracts at the present dose and form did not affect the heart and kidneys of the experimental rats. Furthermore, although both aqueous and ethanolic leaf extracts of V. album exhibited glycemic control in the experimental rats, the extracts did not possess the capacity to restore full therapeutic benefits within the limits of experimental time.…”
Section: Discussionmentioning
confidence: 92%
“…Reduction of serum glucose [505] Stem bark extract Reduction in the blood glucose levels [505] Zygophyllaceae Peganum harmala Linn.…”
Section: Leaves Extractmentioning
confidence: 99%